Efektifitas Mendengarkan Murattal Al-Qur’an terhadap Kualitas Tidur Mahasiswa Kampus V Universitas Negeri Padang - El Firas Ashshiddiqiy, Walid; Irna Aviani, Yolivia (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
The effectiveness of listening recitation murattal Al-Qur’an on student’s sleep qualities in the fifth campus of state university of padang. The purpose of this study to perceive the effectiveness of listening recitation murattal Al-Qur’an on the student’s sleep qualities. One group pretest-posttest without control group was used as the research design as well as a quasi-experimental type. The subjects of this study were male students of the state University of Padang in the fifth campus with range of ages from 18 to 21 years. Paired Sample was used in analyzing research data with the SPSS software for windows assistance. The pretest measurement of the average value is 29,57 while the average value of posttest measurement is 21,28. These result indicate different scores before and after listening to murattal Al-Qur’an’s treatment. In addition, the effect size test was performed to see what extent listening to the murattal Al-Qur’an before bed influence student’s sleep qualities and possessed 1,67 > 0,8 score. That result indicates that listening to murattal Al-Qur’an is effective in improving the student’s sleep qualities